GAYA KOMUNIKASI INTERPERSONAL ORANGTUA DALAM MENCEGAH PENYALAHGUNAAN NARKOBA PADA REMAJA DI DESA CINTA RAKYAT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Liana Hutapea (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
This paper examines the interpersonal communication style do parents in preventing drug abuse, barriers to communication styles used inter personal parents in preventing drug abuse and the most effective communication style used parents in preventing drug abuse among adolescents.The style of communication, there are three, namely: Assertive Communication Styles, Non Assertive and Aggressive. Assertive Communication Style This style is characterized by being able to express feelings and self-esteem is based on an ethical mind. Thus, in expressing themselves by giving attention, dignity and respect. Non-assertive style is more indicative of the feelings of fear and hesitation, deny yourself, as well as more beneficial to others. Aggressive Style This style is to dominate in interactions with other people, both verbal and non-verbal. This style is not very effective because no imposition rights of othersWithout conscious parents use communication styles: assertive style, non-assertive and aggressive in communicating to their children to prevent drug abuse. There is no specific time provided parents in communicating to his children, for example, to communicate while watching TV or while doing other activities parents. Emotional closeness and mutual open very important to have parents that what the parents to their children do not give any impression.